Effect of Tabernero's prognostic subgroups or development of neutropenia on survival outcomes of patients with refractory metastatic colorectal cancer (mCRC) treated with trifluridine/tipiracil plus bevacizumab (TASBEV) in real-world practice - Martinez-Lago, Nieves P.; Alonso de Castro, Beatriz; Reboredo Rendo, Cristina; Calleja, Teresa; Gómez-Randulfe Rodríguez, Martín Igor; Silva Diaz, Sofia; Parajó Vázquez, Iria; Mateos Salvador, Maria; Busto Fernandez, Fernando; Grana Suarez, Begona; De la camara, Juan; Reboredo Lopez, Margarita (Journal of clinical oncology, 2023)
99Background: TASBEV, compared with TAS-102, was associated with an improvement in progression-free survival (PFS) with tolerable toxicity in a randomized, open-label phase 2 trial. However, the subgroups of patients who may benefit from long-term TASBEV treatment are unknown. Methods: We conducted a retrospective, observational study of patients (pts) with mCRC refractory or intolerant to standard therapies treated with TAS-102 30-35 mg/m2 twice daily on days 1-5 and 8-12 every 28 days plus BEV 5 mg/kg on days 1 and 15 at University Hospital a Coruña (Spain). Results: We recorded 47 pts treated between July 2019 to June 2022. Median age was 65 years (range 41 - 82 years), 78.7% ECOG PS0-1, 51.1% RASmt, 78.7% of pts had liver and 23.4%, peritoneal metastases; 29.8% time since diagnosis of 1st metastases <18 months and 57.4% poor prognostic Tabernero Subgroup. Previous treatment included 94.3% previous antiVEGF treatment and 74.5% received TAS-102 BEV as 3rd line of treatment. Median of cycles received was 4 (range 1-15 cycles). ORR and DCR were 2.4% and 48.8%, respectively. With a median follow up of 15.7 months, median PFS was 4.3 months (95% CI, 3.4-5.1 months) and median OS was 9.8 months (95% CI, 7.3-12.3 months). Univariate analysis of prognostic factors for progression-free and overall survival are listed in the table. Conclusions: In our series identified that Tabernero's prognostic subgroups or the development of grade 3-4 neutropenia during treatment, among others; identify patients who may benefit from long-term TASBEV treatment. CharacteristicPFS, monthsHR (95% CI)ap-valueaOS, monthsHR (95% CI)ap-valueaMetastatic sites< 37.92.206 (1.1-4.3)0.01617.73.615 (1.5-8.5)0.002> 33.0--8.1--Liver metastasesNo8.40.473 (0.2-1.1)0.08517.70.608 (0.2-1.8)0.357Yes4.0--9.8--Peritoneal metastasesNo5.10.336 (0.2-0.7)0.00311.10.350 (0.2-0.8)0.009Yes2.5--6.2--Time from metastatic disease diagnosis> 18 months4.30.995 (0.5-2.0)0.90110.61.915 (0.9-4.2)0.103< 18 months4.0--8.5--Tabernero prognostic classificationBest10.0-0.021NR-<0.001Good7.9--19.1--Poor3.3--7.7--Neutropenia during treatmentGrade 1-24.02.353 (1.2-4.7)0.0148.12.578 (1.1-5.8)0.018Grade 3-47.911.5